Characterization of the ligand-binding properties of odorant-binding protein 38 from Riptortus pedestris when interacting with soybean volatiles - Guo, Jianglong; Liu, Panjing; Zhang, Xiaofang; An, Jingjie; Li, Yaofa; Zhang, Tao; Gao, Zhanlin (Frontiers in Physiology, 2025)
BackgroundRiptortus pedestris (Fabricius) (Hemiptera: Alydidae) is a major soybean pest throughout East Asia that relies on its advanced olfactory system for the perception of plant-derived volatile compounds and aggregation pheromones for conspecific and host plant localization. Odorant binding proteins (OBPs) facilitate the transport of odorant compounds across the sensillum lymph within the insect olfactory system, enabling their interaction with odorant receptors (ORs).MethodsReal-time quantitative PCR (qRT-PCR) analyses, fluorescence-based competitive binding assays, and molecular docking analyses were applied to assess the expression and ligand-binding properties of OBP38 from R. peddestris.ResultsThe qRT-PCR analyses revealed high levels of RpedOBP38 expression in the antennae without any apparent sex bias, and it was also highly expressed in the adult stage. Recombinant RpedOBP38 was prepared by expressing it in E. coli BL21 (DE3) followed by its purification with a Ni-chelating affinity column. RpedOBP38 was found to bind most strongly to trans-2-decenal (Ki = 7.440) and trans-2-nonenal (Ki = 10.973), followed by β-pinene, (+) -4-terpineol, carvacrol, methyl salicylate, and (-)-carvone. The 3D structure of RpedOBP38 contains six α-helices and three interlocked disulfide bridges comprising a stable hydrophobic binding pocket. In a final series of molecular docking analyses, several polar (e.g., His 94, Glu97) and nonpolar (e.g., Leu29, Ile59) residues were found to be involved in RpedOBP38-ligand binding.ConclusionThese data support a role for RpedOBP38 in the perception of volatiles derived from host plants, providing important insight into the mechanisms that govern olfactory recognition in R. pedestris, thereby informing the development of ecologically friendly approaches to managing R. pedestris infestations.